Détermination de la variation des paramètres biochimiques de la fonction rénale (Urée et créatinine sériques) chez les patients infectés par les virus de l'hépatite B et l'hépatite C. - BOUKHARI, Rabia; BOURAS, Hafsa (My University, 2023)
The determination of biochemical parameters is of paramount importance in the investigation of pathologies, providing valuable information for screening, diagnosis, prognosis, disease monitoring, treatment management and general health promotion. Accordingly, we conducted this work to determine the variation in biochemical parameters of renal function (serum urea and creatinine) during HBV and HCV infection. We carried out a retrospective study on 182 patients who were admitted to the gastroentero- hepatology department of the Mostaganem University Hospital, where we took into account age, gender, serology and biochemical profile. In parallel, an experimental study was conducted at the PTS of the Ain Tedles Public Health Service and the Dr. ITTALHI M. Medical Analysis Laboratory, involving 991 patients to be screened, with HBs- and HCV-positive cases undergoing biochemical analysis. The results of the retrospective study show that 65 patients are included in this study, of whom hepatitis C is present in 46 patients and hepatitis B in 19 patients, with a predominance of males. A study of variations in serum urea and creatinine levels showed, on the one hand, for patients with hepatitis B, a variation expressed in high levels of urea (0.86 g/L) and creatinine (41.9 mg/L) in a cirrhotic patient. On the other hand, 4 hepatitis C patients had postviral CKD, with very high serum urea and creatinine levels (0.54 g/L - 1.71 g/L; 52.31 mg/L - 157.39 mg/L) respectively. The results of the experimental study show that after screening 991 patients for hepatitis B and C, 3 cases were positive, including one hepatitis B case with serum urea and creatinine levels (0.4 g/L; 12.2 mg/L) and one of the other two hepatitis C cases with values above the norm (0.63 g/L and 18.7 mg/L). It is necessary to monitor the variation of these two parameters during the course of hepatitis to prevent renal damage.
Keywords: HBV; HCV; urea; creatinine; kidney damage